The Effects of Vagus Nerve Stimulation on Ventricular Electrophysiology and Nitric Oxide Release in the Rabbit Heart - Allen, Emily; Pongpaopattanakul, Pott; Chauhan, Reshma A.; Brack, Kieran E.; Ng, G. André (Frontiers in Physiology, 2022)
Background Abnormal autonomic activity including impaired parasympathetic control is a known hallmark of heart failure (HF). Vagus nerve stimulation (VNS) has been shown to reduce the susceptibility of the heart to ventricular fibrillation, however the precise underlying mechanisms are not well understood and the detailed stimulation parameters needed to improve patient outcomes clinically are currently inconclusive. Objective To investigate NO release and cardiac electrophysiological effects of electrical stimulation of the vagus nerve at varying parameters using the isolated innervated rabbit heart preparation. Methods The right cervical vagus nerve was electrically stimulated in the innervated isolated rabbit heart preparation (n=30). Heart rate (HR), effective refractory period (ERP), ventricular fibrillation threshold (VFT) and electrical restitution were measured as well as NO release from the left ventricle. Results High voltage with low frequency vagus nerve stimulation (VNS) resulted in the most significant reduction in HR (by -20.6±3.3%, -25.7±3.0% and -30.5±3.0% at 0.1, 1 and 2ms pulse widths, with minimal increase in NO release. Low voltage and high frequency VNS significantly altered NO release in the left ventricle, whilst significantly flattening the slope of restitution and significantly increasing VFT. HR changes however using low voltage, high frequency VNS were minimal at 20Hz (to 138.5±7.7bpm (-7.3±2.0%) at 1ms pulse width and 141.1±6.6bpm (-4.4±1.1%) at 2ms pulse width). Conclusion The protective effects of the VNS are independent of HR reductions demonstrating the likelihood of such effects being as a result of the modulation of more than one molecular pathway. Altering the parameters of VNS impacts neural fibre recruitment in the ventricle; influencing changes in ventricular electrophysiology, the protective effect of VNS against VF and the release of NO from the left ventricle.